Discussion on the Impact of the Green Innovation Strategy on Corporate Financial Performance in The Automotive Sector - Mishra , Anjay Kumar (SAIM Journal of Social Science and Technology, 2025)
The editorial aims to enhance patent application practice among academician by illustrating content structure based on a published Indian patent with application no. 202421099022 dated on 17/01/2025 on name of Dr. Krunal Soni, Dr. Anjay Kumar Mishra, Dr. Shilpy Jindal, Dr. Balaji Survase, Mr.Shruti Balaji Survase, Mr. Shreyash Balaji Survase, Dr. V.Kannan, Dr. Sivaranjanee R, Dr. Jayashree Patil Dake, Dr. K. Karpagambigai, Ms. M. Sindhu and Mrs. D. Divya could be verified from https://iprsearch.ipindia.gov.in/PublicSearch Status titled Discussion on the Impact of the Green Innovation Strategy on Corporate Financial performance in the Automotive Sector The Green Innovation Strategy can improve corporate financial performance in the automotive industry via cost savings, new revenue streams, stakeholder engagement, and strategic partnerships. Implementing sustainable initiatives and investing in futuristic technologies positively impact both corporate financial and environmental health.